Food and Beverage Product Efforts in Maintaining Food Quality in the Restaurant and Room Service of Hotel Chanti Semarang - Meiroha, Adhinda Putri; Dima, Cindy Citya (Surya Hijau Manfaat, 2025)
The research in this thesis is motivated by the increasing development of the hotel industry in Indonesia. Competition in the hotel industry is increasingly fierce due to the many new hotels that have emerged to date. So hotel management should have a mature strategy to be able to compete with new industries and major competing industries. The problem contained in this thesis is in how to maintain consistency in food quality and overcome it complaint guests about the quality of food at Chanti Hotel. The aim of this final assignment is to maintain food consistency and overcome problems complaint guests about food quality, in this research using a qualitative descriptive method based on the author's experience during On The Job Training and also based on previous research sources. The result of this final assignment is how to maintain consistency in food in a hotel, especially in restaurant and room service, and how to overcome a problem complaint guests about the quality of the food. The conclusion of this thesis is that in maintaining consistency in the quality of our food we must comply with standardized recipes.